The Effectiveness of Science Laboratory Management at Junior High School - Arrahma, Annisa; Afiqah, Nurul; Erlinawati, Erlinawati; Randa, Gusti; Linda, Roza; Rahmad, M (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The laboratory is a place to conduct experiments to prove the theories given in class. This research was conducted to look at the effectiveness of management and constraints of managing a science laboratory at the junior high school (SMP) level. This research used a survey research method with a quantitative approach, while the research subjects were the Head of Laboratory Assistants from 4 junior high schools in Riau province, namely SMPN 1, SMPN 3 Kuok sub-district, SMPN 8, and SMPN 43 Pekanbaru. The data was collected by distributing a questionnaire on the effectiveness of management and use of the laboratory which was given to the head of the laboratory with as many as 117 questions. The research results obtained were the level of effectiveness of science laboratory management in the two regions, namely SMPN Kampar Regency obtained an overall average score of 87.4% while SMPN in Pekanbaru received an average result of 49.82%. Overall, the results were obtained by very good category standard value A. However, in reality there are still several problems in laboratory management, resulting in constraints on several indicators such as completeness of tools, and provision of tools and materials and the main problems occur in organizational and administrative indicators with an overall average result of 49, 82% are below the expected standard with a bad category. So it is necessary to re-evaluate and improve administrative and organizational management which is often neglected by school laboratory management so that special attention can be given to further improvements to obtain very good effective results in the future.